Application of Advanced Class Determination System Using K-Means Clustering Method (Case Study: SMK Al-Badar Balaraja) - Perani Rosyani; Fabian Syawali (International Journal of Integrative Sciences, 2023)
This research develops an information system and application program to classify advanced students at SMK Al-Badar Balaraja using K-Means Clustering. The main problems addressed are unclear classification and the absence of criteria for advanced classes. The research aims to design the system, develop the app, and determine advanced classes based on report grades, attendance, achievements, extracurricular activities, and student organization involvement. The K-Means Clustering algorithm is used to classify student data into clusters based on final evaluations. Focusing on 180 grade 11 Office Administration students, the system and app were successfully designed and tested, indicating reliable identification of advanced students. This research contributes to advanced student classification and enhances education quality at SMK Al-Badar Balaraja